PERAN GURU SEBAGAI PENDIDIK DALAM PENGUATAN KARAKTER PEDULI LINGKUNGAN MELALUI PEMBELAJARAN IPAS PADA MATERI EKOSISTEM SISWA KELAS IV DI SD NEGERI 48 PEKANBARU - Siti Nur Khasanah; Elpri Darta Putra (STKIP Subang, 2026)
ABSTRACT The integration of environmental care character into Integrated Science and Social Studies (IPAS) learning still faces several challenges, as classroom instruction has primarily focused on cognitive aspects, while the development of affective and psychomotor domains has not been optimally implemented. In addition, the level of student involvement remains an issue in the learning process. This study aims to describe the role of teachers as educators in strengthening students' environmental care character through IPAS learning on the ecosystem topic for fourth-grade students at SD Negeri 48 Pekanbaru. This research employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation. The validity of the data was ensured through source triangulation and technique triangulation. The findings indicate that the teacher's role as an educator in strengthening environmental care character through IPAS learning on the ecosystem topic has been effectively implemented in the fourth grade at SD Negeri 48 Pekanbaru. Teachers not only acted as lesson planners and learning facilitators but also served as motivators and role models in shaping students' character. The impact of these roles is reflected in the increased awareness among students of maintaining cleanliness and preserving the surrounding environment, which ultimately represents the primary goal of character education.